Tingkat Kebugaran Jasmani Pada Siswa SMA Negeri 2 Tondano Kelas XI - Brayen Efrata Mamahit; Djajaty M. Lolowang; Djoni A. Sunkudon (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Based on researcher observations of SMA Negeri 2 Tondano students, researchers made initial observations by observing SMA Negeri 2 Tondano students. Each student has a different level of physical fitness, seen from whether or not students are active in doing sports, researchers see that there are some students who like to exercise and some who only play during sports. However, most students who like to exercise compared to those who don't like it, researchers saw that when the subject ended, some students continued to play basketball, volleyball, field tennis and athletics, researchers also saw that in the afternoon many students from SMA Negeri 2 Tondano jogged in the stadium but some did not. Descriptive research. Based on the percentage amount (%), for the female sample of the age group 15-16 years out of 23 students 20 people or 87% were in the “Very Bad” category; 2 people or 8.7% were in the “Bad” category while 1 person or 1% was in the “Medium” category. And for the female sample in the age group 17-20 years, totaling 4 students, all or 100% were in the “Very Bad” category.